HUKUMAN MATI BAGI KORUPTOR : SEBUAH DISKURSUS MENDESAK DI MASA KRITIS - Rofii, M. Sya’roni (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2015)
The issue about corruption after a decade of reformation has not brought Indonesia to the point of free corruption zone. The existence of institutions such as KPK has ever cosidered as the spearhead to rid the republic from corruption virus. However, it finally comes upon an anti climax because it doesn’t give a deterrent effect to the doers of corruption. KPK is faced on a difficult situation. It can be seen from the weakening of its authority, while the death penalty for corruptors was still considered by some parties that it is not urgent. Explicitly, the Law of KPK is actually available on the space for the death penalty for corruptors, but it seems that it still has not found the momentum yet. The criminal of corruption is a problem that needs to be solved seriously and it becomesthe problem of law in every country in the world, include Indonesia. The disease of corruption becomes more rampant day by day. The government's seriousness in finding solution about criminal of corruption is that an establishment of Law No. 31 of 1999 changed into Law No. 20 of 2001 about the Eradication of corruption.